Recovery of NMDA receptor currents from MK-801 blockade is accelerated by Mg(2+) and memantine under conditions of agonist exposure - McKay, Sean (Pergamon Press, 2013)
MK-801 is a use-dependent NMDA receptor open channel blocker with a very slow off-rate. These properties can be exploited to ‘pre-block’ a population of NMDARs, such as synaptic ones, enabling the selective activation of a different population, such as extrasynaptic NMDARs. However, the usefulness of this approach is dependent on the stability of MK-801 blockade after washout. We have revisited this issue, and confirm that recovery of NMDAR currents from MK-801 blockade is enhanced by channel opening by NMDA, and find that it is further increased when Mg(2+) is also present. In the presence of Mg(2+), 50% recovery from MK-801 blockade is achieved after 10′ of 100 μM NMDA, or 30′ of 15 μM NMDA exposure. In Mg(2+)-free medium, NMDA-induced MK-801 dissociation was found to be much slower. Memantine, another PCP-site antagonist, could substitute for Mg(2+) in accelerating the unblock of MK-801 in the presence of NMDA. This suggests a model whereby, upon dissociation from its binding site in the pore, MK-801 is able to re-bind in a process antagonized by Mg(2+) or another PCP-site antagonist. Finally we show that even when all NMDARs are pre-blocked by MK-801, incubation of neurons with 100 μM NMDA in the presence of Mg(2+) for 2.5 h triggers sufficient unblocking to kill >80% of neurons. We conclude that while synaptic MK-801 ‘pre-block’ protocols are useful for pharmacologically assessing synaptic vs. extrasynaptic contributions to NMDAR currents, or studying short-term effects, it is problematic to use this technique to attempt to study the effects of long-term selective extrasynaptic NMDAR activation. This article is part of the Special Issue entitled ‘Glutamate Receptor-Dependent Synaptic Plasticity’.